2016
DOI: 10.1158/0008-5472.can-15-1456
|View full text |Cite
|
Sign up to set email alerts
|

STING Promotes the Growth of Tumors Characterized by Low Antigenicity via IDO Activation

Abstract: Cytosolic DNA sensing is an important process during the innate immune response that activates the Stimulator of Interferon Genes (STING) adaptor and induce interferon type I (IFN-I). STING incites spontaneous immunity during immunogenic tumor growth and accordingly, STING agonists induce regression of therapy-resistant tumors. However DNA, STING agonists and apoptotic cells can also promote tolerogenic responses via STING by activating immunoregulatory mechanisms such as indoleamine 2,3 dioxygenase (IDO). Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
231
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(238 citation statements)
references
References 21 publications
5
231
1
1
Order By: Relevance
“…The small-molecule compound DMXAA (also known as vadimezan), which was originally developed as a tumour-vascular disrupting agent, targets STING in mice 204 . Clinical trial results were disappointing but may be explained by the finding that human STING has an amino acid substitution that makes it insensitive to DMXAA 204 Intriguingly, the absence of STING also improves tumour control and CD8 + T cell activity in a mouse model of lung cancer 205 .…”
Section: Targeting Myeloid Cells To Limit Cancermentioning
confidence: 99%
“…The small-molecule compound DMXAA (also known as vadimezan), which was originally developed as a tumour-vascular disrupting agent, targets STING in mice 204 . Clinical trial results were disappointing but may be explained by the finding that human STING has an amino acid substitution that makes it insensitive to DMXAA 204 Intriguingly, the absence of STING also improves tumour control and CD8 + T cell activity in a mouse model of lung cancer 205 .…”
Section: Targeting Myeloid Cells To Limit Cancermentioning
confidence: 99%
“…DNA sensing by the STING pathway can also mediate immune regulatory responses by induction of IFN-stimulated genes (ISG) with immunoregulatory functions like IDO (67). It has been shown that stimulation of the STING pathway in myeloid DCs using DNA nanoparticles induces IDO, which activate Tregs to promote dominant inhibitory T cell regulation (68,69). These data suggest that activation of the STING pathway can induce immune suppressive factors in the tumor microenvironment; thus, an appropriate level of STING pathway activation may be required for optimal antitumor effects.…”
Section: Type I Ifns In the Generation Of Antitumor Immune Responsesmentioning
confidence: 99%
“…It also has been reported in the context of a non-immunogenic transplantable tumor that deficiency of STING increases tumor protection. In this model, activation of STING by DNA or STING agonists promoted tolerogenic responses by induction of indoleamine 2,3 dioxygenase (IDO), which activated Tregs to promote dominant inhibitory T cell regulation [65,66]. A recent study has linked the activation of STING and production of inflammatory cytokines to brain metastasis and chemoresistance [63].…”
Section: The Sting Pathway and Innate Immune Sensing Of Tumorsmentioning
confidence: 99%